Solitary wave interaction with upright thin porous barriers. (15th January 2023) - Francis, Vivek; Rudman, Murray; Ramakrishnan, Balaji; Loh, Sean; Valizadeh, Alireza
Abstract: The interaction of fluid flow with porous barriers has numerous practical applications, including as a partial barrier to water waves that damp some of the approaching energy at the same time as allowing environmental flow. However, surprisingly little effort has been expended on understanding the fundamentals of this interaction. Therefore, this study aims to model the interaction between waves and thin, upright porous barriers. This is undertaken by modelling the porous barrier empirically within a Smoothed Particle Hydrodynamics (SPH) framework that is then used to model wave flume experiments. Although detailed modelling of the interaction is possible at the laboratory scale, it is not feasible in practical settings where a barrier will contain many thousands of holes that cannot be individually modelled. The key information needed to model the barrier empirically is obtained from solitary wave-porous barrier interaction experiments. Our results indicate that, for each barrier, irrespective of the properties of the wave interacting with it, there is a coefficient value that is able to account adequately for the energy dissipation by the barrier. The reliability of the approach has been demonstrated by comparing SPH model predictions against companion sinusoidal wave-porous barrier experimental measurements. The SPH model was then used to determine the energy dissipation characteristics of porous barriers kept at different draught to water depth ratio, D / d, without reference to the wave flume experiments. Simulation results indicate that barriers are more effective in dissipating the incident wave energy if its draught is over 75% of the water depth. Highlights: For each barrier there exists a coefficient that accounts for its energy dissipation. Calibrated SPH model predictions are in excellent agreement to measurements. SPH results show that the maximum energy dissipation occurs within the 10%–20% range. Porous barriers are most effective if its draught is over 75% of the water depth.